2022
DOI: 10.1097/bpo.0000000000002121
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Negative Online Reviews of Pediatric Orthopaedic Surgeons

Abstract: Background: The growing focus on subjective patient experiences has created an increase in popularity for physician rating websites. The purpose of this study was to characterize extremely negative reviews of pediatric orthopaedic surgeons. Methods: Pediatric orthopaedic surgeons were randomly selected using the Pediatric Orthopaedic Society of North America comprehensive list of surgeons. A search was then performed on Healthgrades.com, Vitals.com, and Yelp.com for 1-star reviews. Reviews were classified into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, this did not change the regional breakdown of complaints, the breakdown of private versus academic complaints, or surgical versus nonsurgical patients. The main conclusions and discussion points from the study remained accurate and relevant and similar methodology has been used in prior studies outside of spine surgery 44,45 . Additional limitations relate to reviewer anonymity.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, this did not change the regional breakdown of complaints, the breakdown of private versus academic complaints, or surgical versus nonsurgical patients. The main conclusions and discussion points from the study remained accurate and relevant and similar methodology has been used in prior studies outside of spine surgery 44,45 . Additional limitations relate to reviewer anonymity.…”
Section: Discussionmentioning
confidence: 73%
“…The main conclusions and discussion points from the study remained accurate and relevant and similar methodology has been used in prior studies outside of spine surgery. 44,45 Additional limitations relate to reviewer anonymity. Firstly, deeper sociological data is unavailable, which makes the geographic findings difficult to assess more conclusively.…”
Section: Discussionmentioning
confidence: 99%
“…The methods of our study were adapted from previous studies examining negative Yelp.com reviews of total joint arthroplasty surgeons, orthopaedic pediatric surgeons, and orthopaedic sports surgeons. [14][15][16] A search was performed using the keywords "hand surgery" on Yelp.com for eight major metropolitan areas including Washington, DC, Dallas, New York, Phoenix, Los Angeles, San Francisco, Boston, and Seattle. The surgeon who the review was directed at was confirmed to be an accredited orthopaedic surgeon performing hand and/or wrist surgery through a secondary internet search using physician Web sites, vitals.com, Angie's list, hospital group Web sites, and/or Doximity.…”
Section: Methodsmentioning
confidence: 99%
“…These unexpected bills are a common complaint among patients according to various studies analyzing common complaints in various healthcare settings. [4][5][6][7] Price transparency for medical services in the United States has been a concern for decades. 8 However, as negotiations between insurers and healthcare systems are often kept private, it may be difficult to accurately inform patients regarding accurate medical procedure pricing.…”
mentioning
confidence: 99%